Characterizing the Expenditure Uncertainties of Industrial Countries in the 21st Century - Heller, Peter (IMF Working Papers; Working Paper, 2005)
A number of uncertainties about long-term expenditure commitments in industrial countries are examined: (i) the assumptions underlying the projections, (ii) the potential to further reduce non-age-related expenditures, (iii) the implicitly assumed absence of "shocks," and (iv) the potential for raising revenue. This paper concludes that (i) there is scope, but within narrow limits, to reduce non-age-related expenditures; (ii) fiscal policy frameworks tend to understate risks; and (iii) prevailing tax rates leave little room for increasing taxation in the countries facing the strongest aging pressures. In sum, governments will have to adopt a much more ambitious fiscal policy stance to cope with aging populations.